Anti-CCP Antibodies Are Not Associated with Familial Mediterranean Fever in Childhood. (9th September 2013) - Onur, Hatice; Aral, Hale; Arica, Vefik; Bercem, Gamze; Usta, Murat; Kasapcopur, Özgur
Abstract : Objective . Anticyclic citrullinated peptide antibodies (anti-CCP) testing is useful in the diagnosis of rheumatoid arthritis (RA) with high specificity. Arthritis is a very common clinical manifestation in children with familial Mediterranean fever (FMF). The aim of the study was to show the presence of anti-CCP antibodies in child individuals diagnosed with FMF. Material and Methods . The study groups comprised one hundred and twenty-six patients (126) diagnosed with FMF (female/male (n ): 66/60) and 50 healthy controls (female/male (n ): 25/25). Clinical and laboratory assessments of the FMF patients were performed during attack-free periods. Erythrocyte sedimentation rate (ESR), serum C-reactive protein (CRP), fibrinogen, and anti-CCP antibody levels were measured. Results . Anti-CCP was negative in healthy controls and also in all FMF patients. There was not a significant difference in anti-CCP between the patient and the control groups. Our study has shown that anti-CCP was correlated moderately with age (rs = 0.271 ;P = 0.0020 ), duration of illness (rs = 0.331 ;P < 0.0001 ), and colchicine therapy (rs = 0.259 ;P = 0.004 ). Conclusion . Our data show that anti-CCP antibodies are not associated with FMF. Anti-CCP does not have a priority for identifying FMF arthritis from the other inflammatory arthritis.